Well-deserved responsible and scientific authorship - Octavio Martínez Betancur (Revista de la Facultad de Medicina, 2007)
Complex and multidisciplinary investigation is a cause of multiple co-authorships. Actually, it is necessary a great number of collaborators to accomplish a scientific work. When it is time to publish the article, it is difficult to resolve the dilemma between credits and responsibility, neither applying editorial standards. More difficulties are added when researchers are pressed by academic and research institutions to growth up the number of their publications, which may impel them to improper conducts in order to get undeserved authorships. Alternatives to dissipate the authorship tension (credits vs. responsibility) do not inspire solutions. More than group or institutional politics or international restrictive norms, which scientific authorship needs are foundational ethics values: honesty, trustworthy and fairness.